Acute severe heart failure in pregnancy: A clinical challenge and review of the literature. (September 2022) - Ellison, Lili; Sundaram, Ash; Coroyannikis, Christina; Cauldwell, Matthew
Pregnancy-associated myocarditis is uncommon and remains poorly described. The spectrum of the disorder is wide, with the severe cases culminating in heart failure, cardiogenic shock and even maternal death. Diagnosis is typically made on imaging, serology and endocardiac biopsy findings with treatment being directed towards the underlying cause. We describe a case of likely peripartum myocarditis associated with severe early-onset pre-eclampsia.